2021
DOI: 10.3390/s21227662
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Based Spectral Super-Resolution of Panchromatic Night-Time Light Imagery: City-Size-Associated Neighborhood Effects

Abstract: Data on artificial night-time light (NTL), emitted from the areas, and captured by satellites, are available at a global scale in panchromatic format. In the meantime, data on spectral properties of NTL give more information for further analysis. Such data, however, are available locally or on a commercial basis only. In our recent work, we examined several machine learning techniques, such as linear regression, kernel regression, random forest, and elastic map models, to convert the panchromatic NTL images in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(59 reference statements)
1
1
0
Order By: Relevance
“…With The result was consistent with the conclusions of most relevant studies [23,24]. In addition, it was concluded that the diagnostic sensitivity (95.34%), specificity (75%), and accuracy (94.44%) of SR-CNN algorithm-based MRI images were obviously superior to those of conventional MRI (81.40%, 50%, and 80%).…”
Section: Discussionsupporting
confidence: 87%
“…With The result was consistent with the conclusions of most relevant studies [23,24]. In addition, it was concluded that the diagnostic sensitivity (95.34%), specificity (75%), and accuracy (94.44%) of SR-CNN algorithm-based MRI images were obviously superior to those of conventional MRI (81.40%, 50%, and 80%).…”
Section: Discussionsupporting
confidence: 87%
“…The further analysis reveals the existence of a fundamental tradeoff between complexity and simplicity in high-dimensional spaces (Gorban et al, 2020) and effectively uses the geometry of few-shot learning (Tyukin et al, 2021c). Among the important tasks for creating practical AI, it is important to note the development of new methods (Akinduko et al, 2016;Mirkes et al, 2022;Zhou et al, 2022) and tools (Rybnikova et al, 2020(Rybnikova et al, , 2021Bac et al, 2021) for creation of AI systems.…”
mentioning
confidence: 99%